Pelaksanaan Peraturan Pemerintah No. 9 Tahun 1975 dalam Perspektif Sosiologi dan Antropologi Hukum Islam - Muchimah Muchimah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2018)
Government Regulation No. 9 of 1975 related to the implementation of marriage was made to support and maximize the implementation of Law No. 1 of 1974 which had not yet proceeded properly. This paper examines Government Regulations related to the implementation of marriage from the perspective of sociology and anthropology of Islamic law. Although the rules already exist, some people still carry out marriages without being registered. This is anthropologically the same as releasing the protection provided by the government to its people for the sake of a rule. In the sociology of Islamic law, protection is a benchmark for the assessment of society in the social environment. Therefore the purpose of this paper is to find out how the implementation of marriage according to PP. No. 9 of 1975 concerning the Marriage Law in the socio-anthropological perspective of Islamic Law.